Direct Self Control for Open-End Winding Interior Permanent Magnet Synchronous Motor using Dual Magnetic Flux Frame - Park, Hyeon Jun; Lee, Hyung Woo; Lee, Kyo Beum (SCEMS 2022 - 2022 IEEE 5th Student Conference on Electric Machines and Systems, 2022)
This paper proposes improved direct self control (DSC) by using a dual magnet flux frame for open-end winding interior permanent synchronous magnet motor (OEWIPMSM). The conventional DSC has advantages of having fast torque response and low switching frequency due to the magnetic flux and torque being directly controlled by a single flux frame and torque hysteresis controller. However, the magnetic flux ripple, current ripple and torque ripple are large. Since the stator magnetic flux trajectory is formed hexagonal shape in stationary reference frame. In this study, a dual magnetic flux frame is applied to overcome this problem. The proposed DSC reduces stator magnetic flux ripple by forming the magnetic flux trajectory into a dodecagon shape in stationary reference system. To form this magnetic flux trajectory, the voltage vector space is divided into 12 sectors, and switching states are selected through comparing dual magnetic flux frame and reference magnetic flux. The validity and effectiveness of the proposed DSC are verified through simulation results.
Keywords: Direct self control; Dual magnetic flux frame; Fast torque response; Flux ripple; Flux trajectory; Interior permanent magnet synchronous motor; Low switching frequency; Magnet motors; OEW-IPMSM; Open-end windings; direct self control; dual magnetic flux frame; flux trajectory; OEW-IPMSM